2012
DOI: 10.1332/174426412x654068
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of knowledge brokering for evidence-informed public health policy and practice: three years of the Scottish Collaboration for Public Health Research and Policy

Abstract: Despite a burgeoning literature on, and widespread interest in, knowledge translation and exchange in public health, few articles provide an account of the actual experiences of knowledge brokerage organisations. The Scottish Collaboration for Public Health Research and Policy (SCPHRP) was formed in 2008 to: identify public health interventions that equitably address major health priorities; foster collaboration between public health stakeholders; and build capacity for collaborative intervention research. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 0 publications
3
18
0
Order By: Relevance
“…This is similar to Frost et al . who noted that the Scottish Collaboration for Public Health Research and Policy (SCPHRP) acting as KB was successful in bringing together academics, health care professionals, the voluntary sector, educationalists and policymakers in a Scottish forum that encouraged knowledge translation …”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…This is similar to Frost et al . who noted that the Scottish Collaboration for Public Health Research and Policy (SCPHRP) acting as KB was successful in bringing together academics, health care professionals, the voluntary sector, educationalists and policymakers in a Scottish forum that encouraged knowledge translation …”
Section: Resultssupporting
confidence: 75%
“…It was reported that the coordinators at the centre, acting in the position of knowledge brokers, developed strategies that brought the researchers and policy group members in perspectives with each other. This is similar to Frost et al 26 who noted that the Scottish Collaboration for Public Health Research and Policy (SCPHRP) acting as KB was successful in bringing together academics, health care professionals, the voluntary sector, educationalists and policymakers in a Scottish forum that encouraged knowledge translation. 26 In Burkina Faso, Hamel and Schrecker 27 elucidated that the Burkina Faso Public Health Association brokered knowledge between researchers and the Burkinabe people by transferring research findings for use in promoting public health.…”
Section: Effectiveness Of Knowledge Brokering -Impactsupporting
confidence: 74%
“…Investigations of knowledge mobilisation processes have been dominated by discussions of boundary spanning and knowledge brokering (Bielak, Campbell, Pope, Schaefer, & Shaxson, 2008;Cooper, 2014;Currie & White, 2012;Dobbins et al, 2009;Frost et al, 2012;Hargadon, 2002;Kislov, Hodgson & Boaden, 2016;Knight & Lightowler, 2010;Lomas, 2007;Meyer, 2010;Schlierf & Meyer, 2013;Waring, Currie, Crompton, & Bishop, 2013;Ziam, Landry, & Amara, 2012). In much of the literature knowledge brokers are characterised as being 'in between worlds'.…”
Section: Connecting Practitioner-research With Knowledge Mobilisationmentioning
confidence: 99%
“…Literature on evidence-informed policies points to "knowledge brokering" as a promising strategy for bridging this know-do gap between research and decisionmaking process (Dobbins et al, 2009;Frost et al, 2012;Lomas, 2007;Meyer, 2010;Olejniczak et al, 2016).…”
mentioning
confidence: 99%